Where majesty death reigns…. in the light of 19th century funeral rites - Raińska, Kinga (Requiem, 2025)
Human’s approach to dying as an event belonging to two orders of human life, nature and culture, has evolved over the centuries. Death as such has always been at the center of religion and its rituals, philosophical considerations, moral judgments and artistic representations, but each era has created its own way of observing, accepting, expressing and describing it. Rituals related to a person’s departure from this world included the time of dying, preparing the body of the deceased for the last journey, as well as funeral and mourning ceremonies. In the 19th century, the ritual of final farewell became a common experience, independent of origin and material status, just like the presence of customs organizing an individual’s life from birth to death. In the new conditions, the phenomenon of democratization of funeral customs, individualization of the memory of the deceased, and separation of the space of life from the sphere of death were born.